2014
DOI: 10.1038/ncomms4182
|View full text |Cite
|
Sign up to set email alerts
|

Coalescence of bubbles and drops in an outer fluid

Abstract: When two liquid drops touch, a microscopic connecting liquid bridge forms and rapidly grows as the two drops merge into one. Whereas coalescence has been thoroughly studied when drops coalesce in vacuum or air, many important situations involve coalescence in a dense surrounding fluid, such as oil coalescence in brine. Here we study the merging of gas bubbles and liquid drops in an external fluid. Our data indicate that the flows occur over much larger length scales in the outer fluid than inside the drops the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

29
229
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(262 citation statements)
references
References 32 publications
29
229
4
Order By: Relevance
“…However, the delicate and ephemeral nature of microbubble coalescence poses significant technical challenges to the precise quantification. In spite of the few important attempts through experimental [26][27][28] and radiological measurements 29 , the fundamentals of coalescence dynamics associated with hydrodynamics and mass transport, including the temporal/spatial scales, have not been well understood. For example, "coalescence preference" has been a puzzling tendency observed in experimentation 29,30 for the merged bubble to be preferentially located closer to the larger of its two parent bubbles.…”
Section: Introductionmentioning
confidence: 99%
“…However, the delicate and ephemeral nature of microbubble coalescence poses significant technical challenges to the precise quantification. In spite of the few important attempts through experimental [26][27][28] and radiological measurements 29 , the fundamentals of coalescence dynamics associated with hydrodynamics and mass transport, including the temporal/spatial scales, have not been well understood. For example, "coalescence preference" has been a puzzling tendency observed in experimentation 29,30 for the merged bubble to be preferentially located closer to the larger of its two parent bubbles.…”
Section: Introductionmentioning
confidence: 99%
“…Paulsen et al used an electrical method and high-speed imaging to describe the droplets coalescence. They showed that the outer uid had a small e ect on the coalescence dynamics [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…After magnification, the image on the scintillator was captured by a CMOS camera (1,024 × 1,024 pixels; Photron SA 1.1, Photron) that was synchronized with the fast rotary stage and a fast shutter. For synchronization, NaCl was dissolved in pure water to be saturated salt water with 26 % by mass, to become electrically conductive, as suggested in other studies 3,4 . The whole imaging system was carefully aligned to gravity by using a digital inclinometer with 0.001…”
mentioning
confidence: 99%
“…Early-time growth of the liquid bridge that accompanies coalescence driven by Laplace pressure has long been a central topic in fluid dynamics with the aim of understanding the relevant coalescence mechanisms. The liquid-bridge growth has been interpreted theoretically throughout integral description in Stokes flow 1 and experimentally with high-speed optical imaging 2 and electrical methods 3,4 . However, asymmetric coalescence between different-sized drops [5][6][7][8] has been poorly investigated so far, although it is essential to understand various processes such as partial coalescence [9][10][11] , bubble bursting 12,13 and spreading [14][15][16][17] .…”
mentioning
confidence: 99%
See 1 more Smart Citation